Determinan dan Peran Kualitas Sistem Informasi Akuntansi Terhadap Akuntabilitas Keuangan Organisasi Perangkat Daerah - Karyanto, Karyanto; Sofyani, Hafiez (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to empirically test the determinants and role of the quality of accounting information systems on the financial accountability of regional apparatus organizations Methodology/approach: This research uses samples from OPD in Yogyakarta City. Respondents in this study consisted of 180 people who were SIA users. Data was collected through a questionnaire using a Likert scale. Data analysis was carried out using the CMB test, descriptive statistics, validity test, reliability test, and hypothesis test Findings: The results of the research show that the determinants of AIS are the availability and function of software; network availability and function have a positive influence on AIS quality, while hardware availability and function, adaptability and involvement have no effect on AIS quality. A SIA that has good quality will increase financial accountability Practical implications: In practice, this research is able to provide new insights regarding AIS literacy which influences financial accountability and provides considerations for stakeholders to pay attention to AIS determinations which influence financial accountability Originality/value: The novelty of this research is that there are still very few who have conducted research related to the determinants of AIS quality on financial accountability, especially in OPD. Most AIS research is conducted in the private sector and much focuses on linking AIS with company performance